1. Find the equation of tangent line of curve x(y^2)-2(x^2)y=6 at (-2,3)
Differentiate implicitly,
y^2 + x(2y)y' - 4xy - 2x^2y' = 0
Plug in given numbers: x = -2, y = 3
9 - 12y' + 24 - 8y' = 0
Solve for y',
y' = 33/20
Therefore, the equation of tangent line can be written as
y - 3 = (33/20)(x+2)
2. Find the point at curve y=-1/3(x^2)+3 having the minimum distance to point (1,1) and compute the distance.
Pick a point (x, y) from the curve. Let D be the distance from (1,1) to (x,y).
D^2 = (x-1)^2 + (y-1)^2 ......(1)
Differentiate (1) with respect to x,
2D dD/dx = 2(x-1) + 2(y-1)y' = 0 ......(2)
Simplify (2) and plug in y-1 = (-1/3)x^2+2 and y' = (-2/3)x,
x-1 + [(-1/3)x^2+2](-2/3)x = 0
Solve for x,
x = 1.9510
y = (-1/3)x^2 + 3 = 1.7312
D = √[(x-1)^2 + (y-1)^2] = 1.12 (the minimum distance)
2006-12-31 15:31:01
·
answer #1
·
answered by sahsjing 7
·
0⤊
0⤋
1. Find the equation of tangent line of curve x(y^2)-2(x^2)y=6 at (-2,3).
The tangent line will have the same slope as the curve at (-2,3). So find the derivative at the point (-2,3). Differentiate implicitly.
y² + 2xy(dy/dx) - 4xy - 2x²(dy/dx) = 0
(2xy - 2x²)(dy/dx) = -y² + 4xy
dy/dx = (-y² + 4xy)/(2xy - 2x²)
at (-2,3)
dy/dx = (-3² + 4(-2)(3))/(2(-2)(3) - 2(-2)²)
dy/dx = (-9 - 24)/(-12 - 8) = -33/-20 = 33/20
So the equation of the tangent line at (-2,3) is
y - 3 = (33/20)(x + 2)
y = (33/20)x + 33/10 + 3
y = (33/20)x + 63/10
2006-12-31 16:53:23
·
answer #2
·
answered by Northstar 7
·
0⤊
0⤋
1. x(y^2) - 2(x^2)y = 6 at (-2, 3)
First thing you do is differentiate implicitly, with respect to x.
(y^2) + x(2y)(dy/dx) - 2[2xy + (x^2)(dy/dx)] = 0
Simplifying even more, we get
(y^2) + 2xy(dy/dx) - 4xy - 2x^2(dy/dx) = 0
Move everything with a (dy/dx) to the right hand side,
2xy(dy/dx) - 2x^2(dy/dx) = -y^2 + 4xy
Factor (dy/dx) on the left hand side.
(dy/dx) [2xy - 2x^2] = -y^2 + 4xy
Now, isolate dy/dx by dividing 2xy - 2x^2 both sides.
(dy/dx) = [-y^2 + 4xy]/[2xy - 2x^2]
Let's factor the top and bottom to see if anything cancels. If not, the answer will be cleaner nonetheless anyway.
(dy/dx) = [-y(y - 4x)] / [2x(y - x)]
(dy/dx) = [y / (2x)] [4x - y]/[y - x]
In order to find the equation of the tangent line, we plug in x = -2 and y = 3 in the equation for dy/dx
m = [3/(2*(-2))] [4(-2) - 3]/[3 - (-2)]
m = [-3/4] [-11/5]
m = 33/20
Now that we have the slope, we can use the slope formula to get the equation of the line, letting (x1, y1) = (-2, 3), and
(x2, y2) = (x, y)
(y2 - y1) / (x2 - x1) = m
(y - 3) / (x - (-2)) = 33/20
20(y - 3) = 33(x + 2)
20(y - 3) = 33x + 66
y - 3 = (33/20)x + 33/10
y = (33/20)x + 33/10 + 3
y = (33/20)x + 63/10
2006-12-31 16:59:33
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
#1
1.Take the derivative of the equation.
2. Use the slope formula, (y2-y1)/(x2-x1).
3. Set the slope of each tangent line equal to the derivative and solve for x.
Good luck!!
2006-12-31 15:34:09
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
#1
y' = y^2 + x(2y)y' - 4xy-2(x)^2y' = 0
(y)y^2- 4xy = y' ( 2(x)^2 -x(2y) )
y' = [ (y)y^2- 4xy ] / [ 2(x)^2 -x(2y) ]
plug in the values and then you should get 33/20 which is your slope
your equation using point slope form should there for =
y-3 = 33/20 (x+2)
2006-12-31 15:44:40
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋